2018
DOI: 10.3892/ol.2018.8843
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid activation in carcinogenesis and cancer development: Essential roles of long‑chain acyl‑CoA synthetases (Review)

Abstract: The significance of fatty acid metabolism in cancer initiation and development is increasingly accepted by scientists and the public due to the high prevalence of overweight and obese individuals. Fatty acids have different turnovers in the body: Either breakdown into acetyl-CoA to aid ATP generation through catabolic metabolism or incorporation into triacylglycerol and phospholipid through anabolic metabolism. However, these two distinct pathways require a common initial step known as fatty acid activation. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 61 publications
(109 reference statements)
2
115
0
2
Order By: Relevance
“…3C & S3C). Although ACSL1 and ACSL5 are isozymes with similar catalytic function, genetic knockout studies in mice showed that ACSL5 has a major role in fatty acid biosynthesis and deposition, while ACSL1's function is mostly involved in fatty acid oxidation 34 . A metabolic model based on bulk gene expression data would incorrectly assume that both enzymes are expressed by malignant cells, thus over-estimating the metabolic capabilities of malignant cells.…”
Section: Resultsmentioning
confidence: 99%
“…3C & S3C). Although ACSL1 and ACSL5 are isozymes with similar catalytic function, genetic knockout studies in mice showed that ACSL5 has a major role in fatty acid biosynthesis and deposition, while ACSL1's function is mostly involved in fatty acid oxidation 34 . A metabolic model based on bulk gene expression data would incorrectly assume that both enzymes are expressed by malignant cells, thus over-estimating the metabolic capabilities of malignant cells.…”
Section: Resultsmentioning
confidence: 99%
“…192 Arachidonyl-CoA can be subsequently esterified to form TAGs and incorporated into phospholipids, or utilised as a substrate by COX2 to enhance eicosanoid biosynthesis. 193 ACSL4 is also implicated in the localised release of AA in the mitochondria, and this requires the transport of arachidonyl-CoA to the inner mitochondrial membrane via the translocator protein (TSPO) and hydrolysis by acyl-CoA thioesterase 2 (ACOT2). 192 Importantly, several studies have implicated ACSL4 in tumorigenesis, with advanced-stage breast, colorectal, hepatocellular and prostate carcinomas displaying increased expression at both the mRNA and protein levels.…”
Section: Fatty Acids Support Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…Through regulation of DNA and RNA metabolism, epigenetic modification of pyrimidine metabolism may affect cell cycle, proliferation, and differentiation, including micro-RNAs and noncoding RNAs (Fu & He, 2012). In general, it is believed that the correlation between abnormal metabolism and cancer involves the associations among obesity, inflammation, and cancer cell proliferation, invasion, and angiogenesis (Amiri et al, 2018;Tang, Zhou, Hooi, Jiang, & Lu, 2018). Furthermore, cell cycle can influence cancer progression through mitosis and proliferation of cancer cells (Bai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%